2009
DOI: 10.1264/jsme2.me09102
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Rapid Quantification of Viable Listeria monocytogenes Using Fluorescence in situ Hybridization in Combination with Filter Cultivation

Abstract: We developed a new method that rapidly and specifically enumerates only viable Listeria monocytogenes in food using fluorescence in situ hybridization in combination with filter cultivation (FISHFC). Viable L. monocytogenes could be specifically quantified within 16 h using an Alexa647-labeled mRL-2 probe. The coefficient of the correlation between the new method and the conventional plating method was 0.959.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Shimizu et al (2009) showed that FISHFC was an equally accurate yet faster method than the conventional plate count method when enumerating viable C. perfringens in ground beef. Fuchizawa et al (2009) also showed that FISHFC could be used to enumerate viable L. monocytogenes in smoked salmon and Camembert cheese.…”
Section: Discussionmentioning
confidence: 97%
“…Shimizu et al (2009) showed that FISHFC was an equally accurate yet faster method than the conventional plate count method when enumerating viable C. perfringens in ground beef. Fuchizawa et al (2009) also showed that FISHFC could be used to enumerate viable L. monocytogenes in smoked salmon and Camembert cheese.…”
Section: Discussionmentioning
confidence: 97%
“…There are already FISH procedures developed for Listeria spp. detection, but only a few probes are specific for L. monocytogenes (Almeida et al, 2011;Fuchizawa et al, 2009;Moreno et al, 2011;Wang et al, 1991;Zhang et al, 2012) (Table S1 of supplementary material). Most of the existing probes are not simultaneously specific and sensitive because of the high number of non-target strains or the limited coverage of the target strains.…”
Section: Evaluation Of the L Monocytogenes Probes Described In Litermentioning
confidence: 99%
“…Several 16S or 23S rRNA probes have been developed for the detection of Listeria spp. by FISH methods (Almeida et al, 2011;Brehm-Stecher et al, 2005;Fuchizawa et al, 2008Fuchizawa et al, , 2009Moreno et al, 2011;Schmid et al, 2003;Wang et al, 1991;Zhang et al, 2012) but only a few of them are able to specifically detect L. monocytogenes (Almeida et al, 2011;Fuchizawa et al, 2009;Moreno et al, 2011;Wang et al, 1991;Zhang et al, 2012). These methods have been described as being highly specific and sensitive but there is no comparison between the probes.…”
Section: Introductionmentioning
confidence: 99%
“…They need efficient tools to control this pathogen, in order to comply with food safety regulations while minimizing economic losses. Different rapid methods have been developed for detection of L. monocytogenes such as immunoassays, fluorescent in situ hybridization, amplification methods or impedanciometry (Cho & Irudayaraj, 2013;Fuchizawa, Shimizu, Ootsubo, Kawai, & Yamazaki, 2009;Labrador, Rota, Pérez, Herrera, & Bayarri, 2018;Rodriguez-Lazaro, Gonzalez-Garcia, Gattuso, Gianfranceschi, & Hernandez, 2014). The impedance method…”
Section: Introductionmentioning
confidence: 99%